Characterization of Flexible Multi-Walled Carbon Nanotubes Network Sensor to Freon Gas Detection - Al-Makram, Nisreen M.; Saleh, Wasan R. (Iraqi Journal of Science, 2021)
MWCNTs-OH was used to prepare a flexible gas sensor by deposition as a network on a filter cake using the method of filtration from suspension (FFS). The morphological and structural properties of the MWCNTs network were characterized before and after exposure to Freon gas using FTIR spectra and X-ray diffractometer, which confirmed that the characteristics of the sensor did not change after exposure to the gas. The sensor was exposed to a pure Freon134a gas as well as to a mixture of Freon gas and air with different ratios at room temperature. The experiments showed that the sensor works at room temperature and the sensitivity values increased with increasing operating temperature, to be 58% until 150 ºC. The fabricated flexible sensor has good response and recovery times at low gas concentrations of 1.3, 2, and 2.7 ppm.